2017
DOI: 10.1080/11745398.2017.1415152
|View full text |Cite
|
Sign up to set email alerts
|

An eco-feminist perspective on the co-existence of different views of seals in leisure activities

Abstract: This study adopts an eco-feminist perspective and investigates leisure activities involving seals occurring in the area of Tromsø, an Arctic town in Norway. The aim is to contribute to the discussion of the existence of various conceptualisations of wild animals, with particular attention to their implications in terms of animal welfare and wellbeing, and the promotion of specific ways we as humans view wild animals and ourselves. The data was collected through promotional material, local media and history lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Recently, some tourism scholars have discussed the use of animals in tourism from an ethical perspective, and some have explicitly adopted and discussed the Ecofeminism approach (Bertella, 2013, 2014, 2017, 2018; Burns, 2015, 2017; Burns et al , 2011; Cohen, 2009; Fennell, 2012a, 2012b, 2012c, 2013a, 2013b; 2014; Markwell, 2015; Shani and Pizam, 2008; Yudina and Fennell, 2013; Yudina and Grimwood, 2015). With regard to wildlife tourism, Yudina and Grimwood (2015, p. 731) investigate polar bear watching.…”
Section: Wild Animals From An Ecofeminist Perspectivementioning
confidence: 99%
“…Recently, some tourism scholars have discussed the use of animals in tourism from an ethical perspective, and some have explicitly adopted and discussed the Ecofeminism approach (Bertella, 2013, 2014, 2017, 2018; Burns, 2015, 2017; Burns et al , 2011; Cohen, 2009; Fennell, 2012a, 2012b, 2012c, 2013a, 2013b; 2014; Markwell, 2015; Shani and Pizam, 2008; Yudina and Fennell, 2013; Yudina and Grimwood, 2015). With regard to wildlife tourism, Yudina and Grimwood (2015, p. 731) investigate polar bear watching.…”
Section: Wild Animals From An Ecofeminist Perspectivementioning
confidence: 99%
“…The form of labor that they provide varies. In the above sections, animals featured in various roles, including: A kind of spiritual commodity [ 73 ], including serving as totem animals; A mode of transportation, such as donkey treks or dog-sledding in the Arctic; A laborer in the background to a more center-stage tourism activity [ 32 ], such as how research has found that having wolves in an area where hunting tourists hunt herbivores adds to the overall experience [ 45 ], or goats in the background to a farmers’ market; A culinary delight [ 30 ], such as alligator meat in Louisiana [ 5 ]; A front-stage performer, such as animals doing tricks in circuses [ 27 ]; A marker of place, such as the kangaroo or koala for Australia [ 11 ]; A “facilitator” of leisure [ 13 ], such as an animal trained to serve drinks; The face of a souvenir or toy [ 5 , 43 ]; The ultimate sacrifice as a game animal to be hunted as part of the Big Five. …”
Section: Discussionmentioning
confidence: 99%
“…Given this, one might ask whether travel may increase, but travel-associated accumulation (such as physical souvenirs) may decrease. As tourism becomes a ritual context for showing identity-based goods, moreover, animal tourism experiences may be valuable to establishing a person’s status [ 43 , 44 ]. Within this, last-chance tourism, danger tourism and slum tourism in relation to interacting with animals may feasibly be on the rise among some tourists [ 3 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a growing body of (eco)feminist post-humanist work that has begun to explore more-than-human leisure relations with nature, 'the environment'and non human animals (Bertella 2018;Finkel & Danby 2018;Dashper, 2016). This work questions the assumed mastery of nature and hierarchical separation of human bodies from the fleshy and non-organic composition of our shared life worlds.…”
Section: Silences Frictions and Feminist Futuresmentioning
confidence: 99%